A pro-inflammatory microenvironment triggers overexpression of tumor-related RAC1B in polarized colorectal cancer cells - Joana, Pereira (2022)
An inflammatory microenvironment is a tumor-promoting condition that provides survival signals to which cancer cells respond with changes in their gene expression. One key regulatory mechanism is alternative splicing. For example, RAC1B is a RAC1 alternative splicing variant that we previously identified in a subset of BRAF-mutated colorectal tumors and that was found increased in colon mucosa under inflammatory conditions, such as samples from inflammatory bowel disease patients or following experimentally-induced acute colitis in a mouse model. Based on these findings, the main goal of this work was to determine which pro-inflammatory signals from stromal cells lead to an increase in RAC1B expression levels in colorectal cancer (CRC) cells. For this, we used a physiologically relevant epithelium-like monolayer of fully polarized Caco-2 CRC cells grown on porous membrane inserts, and then co-cultured underneath with stromal cells, including fibroblasts, monocytes and macrophages. RAC1B expression was analyzed in Caco-2 cells by RT-qPCR, Western blot and confocal fluorescence microscopy. Co-culture experiments revealed that the combined presence of cancer-associated fibroblasts and/or M1 macrophages induced an increase in RAC1B levels in Caco-2 cells, accompanied by a loss of epithelial organization. Moreover, using a human inflammation antibody array, we were able to identify from the conditioned co-culture media that cytokine IL-6 was associated with increased RAC1B expression. Remarkably, the incubation of polarized Caco-2 cells with purified IL-6 was sufficient per se to trigger an increase in RAC1B expression in a dose-dependent manner, and the presence of anti-IL-6 antibodies during the co-culture prevented the increase. Overall, our data indicate that pro-inflammatory signals from the microenvironment can modulate RAC1B expression in colon epithelial cells. Since RAC1B was shown to sustain tumor cell survival and promote escape form oncogene-induced senescence, the data further strengthen the causal connection between inflammatory conditions and the development of colorectal cancer.